Development and Validation of the Islamic Work Exemplary Scale in Indonesia - Sumin Sumin; Heri Retnawati; Wajidi Sayadi (Islamic Guidance and Counseling Journal, 2023)
The ethical and moral crisis in Indonesia has spread to the work environment, as evidenced by the high level of fraud and abuse of power. This phenomenon requires effective solutions, one of which is Islamic Work Exemplification. This concept is relevant to Indonesia as a country with the largest Muslim population and aligns with universal ethical principles. The main challenge is to implement and measure these principles in daily behavior. Although many studies have shown the influence of religion on work ethics, researchers have yet to make a serious effort to develop and validate the Islamic Work Exemplary Scale. This study aims to develop, validate, and estimate the reliability of the Islamic Work Exemplary Scale. An exploratory method based on a quantitative approach was used in this study. Respondents as scale test subjects were randomly selected from as many as 453 employees from Indonesia's government and private sectors. Respondents were divided into two groups: 180 for the small-scale pilot test and 273 for the large-scale pilot test. This study used exploratory factor analysis (EFA) to identify factors and dimensions and confirmatory factor analysis (CFA) to prove validity and reliability. The results showed that of the 37 items tested, 31 were valid and reliable. The items formed four important aspects of Islamic work ethics: honesty, responsibility, professionalism, and religiosity. Although this study has some limitations, the results of this study are important and can be used as a basis for further research on Islamic work ethics.